Thematic mapping of Burundi using geospatial data and satellite images processed by geoinformatics methods - Lemenkova, Polina (Geografares, 2024)
This paper presents the implementation of the integrated cartographic approach for environmental mapping of Burundi, East Africa. Monitoring different types of land cover in Africa by remote sensing is presented using GRASS SIG methods. The series of thematic maps of vegetation and habitat types, landscapes, topographic, geomorphic and geological context of Burundi is created in QGIS and GMT software. The methodological issues concerning the processes of cartographic scripting are discussed with commented snippets of programming codes using syntax of GRASS GIS. Several modules are used for satellite image mosaic, processing vector and raster data, and classification. The paper documents environmental features of Burundi, such as vegetation types, land cover patterns, geologic setting and landscape distribution using digital cartographic tools. A series of the thematic maps is proposed to support environmental policies on agricultural management in Burundi.